Tezcatlipoca: trickster and supreme deity - Baquedano, Elizabeth, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2014)
Tezcatlipoca: Trickster and Supreme Deity brings archaeological evidence into the body of scholarship on the lord of the smoking mirror," one of the most important Aztec deities. While iconographic and textual resources from sixteenth-century chroniclers and codices have contributed greatly to the understanding of Aztec religious beliefs and practices, contributors to this volume demonstrate the diverse ways material evidence expands on these traditional sources. The interlocking complexities of Tezcatlipoca's nature, multiple roles, and metaphorical attributes illustrate the extent to which his influence penetrated Aztec belief and social action across all levels of late Postclassic central Mexican culture. Tezcatlipoca examines the results of archaeological investigations--objects like obsidian mirrors, gold, bells, public stone monuments, and even a mosaic skull--and reveals new insights into the supreme deity of the Aztec pantheon and his role in Aztec culture.--Provided by publisher.
Introduction: Symbolizing Tezcatlipoca / Nicholas J. Saunders and Elizabeth Baquedano -- 1. The archaeology of Tezcatlipoca / Michael E. Smith -- 2. Iconographic characteristics of Tezcatlipoca in the representations of central Mexico: the Ezpitzal case / Juan José Batalla Rosado -- 3. Enemy brothers or divine twins?: a comparative approach between Tezcatlipoca and Quetzalcoatl, two major deities from ancient Mexico / Guilhem Olivier, translated by Mihael Besson -- 4. Tezcatlipoca and Huitzilopochtli: political dimensions of Aztec deities / Emily Umberger -- 5. Tezcatlipoca as a warrior: wealth and bells / Elizabeth Baquedano -- 6. Gender ambiguity and the Toxcatl sacrifice / Cecelia F. Klein -- 7. The Maya lord of the smoking mirror / Susan Milbrath.
Keywords: Tezcatlipoca (Aztec deity); Aztecs -- Religion; Aztec mythology